The Method of Qur’anic Exegesis in Indonesian Modern Context: A Study of Hamka’s and Quraish Shihab’s Thoughts on Trinity - Moh. Nailul Muna (SUHUF, 2022)
This paper aims to analyze the modern interpretation method in Indonesia when understanding verses closely related to a concept outside Islamic religion. One of them is Trinity conception criticized by Quran on (5:73-75). Indonesian interpreters explain this passage in a variety of ways and the those are viewed dogmatically; using the method of quoting the Quran and Hadith, the opinion of the Salaf and Mutakallimn scholars. Hamka and Quraish Shihab made a different offer. Hamka in al-Azhar's interpretation tends to read the Quranic criticism using the Bible. Meanwhile, Shihab uses logical reasoning in reading these verses. These two things become new markers of the development of modern Indonesian commentary regarding with objectively reading trinity conception rather than by dogmatic sense. The method used in this research is descriptive-analytical. The results obtained from the two objects of this study are that the methods used by Hamka and Quraish Shihab are intertextuality and reasoning. The two methods allow wider acceptance of the interpretation product, including to non-Muslims.